A cationic thorium-organic framework with triple single-crystal-to-single-crystal transformation peculiarities for ultrasensitive anion recognition - Li, Zi-Jian (2022)
Single-crystal-to-single-crystal transformation of metal-organic frameworks has been met with great interest, as it allows for the creation of new materials in a stepwise manner and direct visualization of structural transitions when subjected to external stimuli. However, it remains a peculiarity among numerous metal-organic frameworks, particularly for the ones constructed from tetravalent metal cations. Herein, we present a cationic thorium-organic framework displaying unprecedented triple single-crystal-to-single-crystal transformations in organic solvents, water, and NaIO3 solution. Notably, both the interpenetration conversion and topological change driven by the SC-SC transformation have remained elusive for thorium-organic frameworks. Moreover, the single-crystal-to-single-crystal transition in NaIO3 solution can efficiently and selectively turn the ligand-based emission off, leading to the lowest limit of detection (0.107 μg kg-1) of iodate, one of the primary species of long-lived fission product 129I in aqueous medium, among all luminescent sensors.